2009
DOI: 10.1016/j.chaos.2009.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal regime transition in a modified minority game model

Abstract: The search for more realistic modeling of financial time series reveals several stylized facts of real markets. In this work we focus on the multifractal properties found in price and index signals. Although the usual Minority Game (MG) models do not exhibit multifractality, we study here one of its variants that does. We show that the nonsynchronous MG models in the nonergodic phase is multifractal and in this sense, together with other stylized facts, constitute a better modeling tool. Using the Structure Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…To address these problems we shall use multifractal techniques known to capture non trivial scale properties as shown by Mandelbrot (a pioneer to find self-similarity in the cotton prices distribution [1,2]); by Evertsz [3], who confirmed the distributional self-similarity and suggested that market self-organizes to produce such feature also; by Mantegna and Stanley [4], who found a power law scaling behavior over three orders of magnitude in the S&P 500 index variation. These works were an important hallmark to shed light in the financial market dynamics [5]. It shows that we can use concepts and tools from statistical mechanics to model and analyze financial data [6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…To address these problems we shall use multifractal techniques known to capture non trivial scale properties as shown by Mandelbrot (a pioneer to find self-similarity in the cotton prices distribution [1,2]); by Evertsz [3], who confirmed the distributional self-similarity and suggested that market self-organizes to produce such feature also; by Mantegna and Stanley [4], who found a power law scaling behavior over three orders of magnitude in the S&P 500 index variation. These works were an important hallmark to shed light in the financial market dynamics [5]. It shows that we can use concepts and tools from statistical mechanics to model and analyze financial data [6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Here we introduce two previous artificial markets which focus on heterogeneity of agents; in Ref. [17], the model reconstructs volatility clustering by considering the heterogeneity of the decision making and Ref [18] is an examples of minority games with heterogeneity.…”
Section: Mixed Learning Speed -The Origin Of Volatility Clusteringmentioning
confidence: 99%
“…An idea of how estimator (8) works is provided in Figure 6: panel (a) displays a trajectory of Z(t, ω) with its increments; panel (b) shows the functional parameter ( , ) t ω H and panel (c) the absolute error of the estimates provided by Once the estimation of H(t,ω) was obtained through (8), we used it to calculate the residuals in the usual way…”
Section: Estimation Of H(t ω)mentioning
confidence: 99%
“…Estimator defined by (8): assumes the increments process X j+q,n -X j,n to be normally distributed within the window δ with mean zero and Figure 6. Sample autocorrelation function of the MPRE variance given by relation (5).…”
Section: Estimation Of H(t ω)mentioning
confidence: 99%
See 1 more Smart Citation